Collateral Damage : Dollar Strength and Emerging Markets' Growth - Druck, Pablo (IMF Working Papers; Working Paper, 2015)
We document that, historically, although stronger growth in the U.S. increases growth in emerging markets, U.S. dollar appreciation (depreciation) cycles-which are highly persistent-mitigate (amplify) the impact on real GDP growth in emerging markets. We argue that the main transmission channel of the latter is through an income effect: as the dollar appreciates, commodity prices fall; weaker commodity prices depress domestic demand via lower real income; real GDP in emerging markets decelerates; and vice versa. These effects hold despite any potential expenditure-switching effect resulting from the relative (to the U.S. dollar) currency depreciation of emerging market economies. We also show the negative effect on emerging markets' growth of U.S. interest rates beyond the effects of the U.S. real exchange rate and real GDP growth. Therefore, at the time of writing, emerging markets' growth is expected to remain subdued reflecting, intera alia, the expected persistence of the strong dollar and the anticipated increased in the U.S. interest rates.